English and international students’ adjustment in Indonesian higher education: A teacher’s perspective - Hamamah; Hapsari, Yulia (JEES (Journal of English Educators Society), 2021)
International students at higher education in Indonesia encounter an extent of situations amid their adaptations in academic life. These experiences contribute to their satisfaction. As handful of studies within Indonesian context were conducted to identify the international students’ difficulties in adapting to academic life, teacher’s point of view toward the issue is barely available. This study centers at a teacher’s experience in dealing with the international students. Highlight is given to language barrier, not only encountered by the international students but also the teacher. A narrative inquiry was employed involving an academic leader who is also a teacher knowledgeable in internationalization agenda in higher education in Indonesia. Results of the study reveals that the academic adaptation of international students, with the focus of language barrier, was compounded by the absence of roadmap of internationalization policy in national and organizational levels, less-ideal classroom setting, and not effective interaction within classroom with the diversity of people involved. It is suggested that the policy on the proficiency of English language should be regulated to be mastered by students and teachers in international program. HIGHLIGHTS: The lack of policy regulating standard of English proficiency level as entry requirement for international students becomes one of the causes of the language barrier problem that might hurdle the academic adaptation of international students. The composition of domestic and international students in a class as well as the lack of English proficiency of both the teacher and the students has contributed to the difficulties in academic adjustment. The study specifically explores a teacher's experience in dealing with international students, emphasizing the teacher's viewpoint on the challenges faced by both students and themselves